Assessment of River Water Quality Using Pollution Index and Development of Pollution Control Strategies in the Petung River, Indonesia - Dewi, Eliza Masita; Kurniawan, Andi; Anggayasti, Wresti Listu; Hasan, Muhammad Fathur Rouf; Wijayanto, Hari Wahyu (Journal of Environmental Engineering and Sustainable Technology, 2025)
The Petung River supports domestic, agricultural, and economic activities in Pasuruan City but is subject to increasing anthropogenic pressures. This study aims to assess the river water quality status and formulate water pollution control strategies. Water quality was evaluated using the Pollution Index based on laboratory measurements conducted in April and June 2025. A SWOT analysis was performed by identifying internal and external factors through field observations and key informant interviews, followed by weighting and ranking to determine strategic priorities. The results indicate that the Petung River is predominantly classified as lightly polluted, with Pollution Index values ranging from 2.48 to 5.06, while one monitoring point in June 2025 reached a moderate pollution status. Although pH (6.75–7.80) and nitrate (1.15–3.40 mg/L) complied with Class II standards, total suspended solids, biological oxygen demand (6.49–16.01 mg/L), chemical oxygen demand, and total phosphate (0.27–3.03 mg/L) exceeded regulatory thresholds. The priority strategy is the establishment of communal wastewater treatment systems, supported by improved coordination, institutional capacity, community-based programs, and strengthened monitoring.